Comparison of the Implementation of Regional Spatial Plans on Environmental Quality in Dewa Ruci and Glagah Beaches, Purworejo Regency - Nur Hasanah; Dr. Rini Fidiyani, S.H., M.Hum. (Universitas Negeri Semarang, 2026)
The Regional Spatial Plan (RTRW) is an instrument in controlling the use of space to maintain environmental sustainability, especially in coastal areas that have a high level of ecological vulnerability. Dewa Ruci Beach and Glagah Beach in Purworejo Regency are developing as coastal tourist areas with differences in the implementation of RTRW that have an impact on environmental quality. This study aims to analyze and compare the implementation of RTRW on environmental quality in the two regions. The research method used is qualitative with a normative juridical approach through a study of Law Number 26 of 2007 concerning Spatial Planning, RTRW regional regulations of Purworejo Regency, as well as laws and regulations related to the management of coastal areas and the environment. Data were obtained through literature studies on primary, secondary, and tertiary legal materials, and supported by indirect observations, limited interviews, and documentation. The analysis was conducted in a comparative descriptive manner to identify similarities, differences, and implications of the implementation of RTRW in both research locations. The results of the study show that the implementation of RTRW at Glagah Beach is relatively more effective and in accordance with the normative provisions of spatial planning, which is reflected in the control of space utilization, coastal boundary protection, and environmental conservation efforts. Meanwhile, the implementation of RTRW at Dewa Ruci Beach still faces obstacles in terms of control and law enforcement, resulting in an impact on the quality of the environment that is less than optimal. This study concludes that the implementation of RTRW normatively has a significant effect on the quality of the coastal environment and requires strengthening supervision and consistency of spatial planning policies.